Intercultural Competence: An exploration of its role in international trade negotiations in the steel-related flat-rolled products industry sector - Kristina Erwig (MA Akademie Verlags- und Druck-Gesellschaft mbH, 2022)
Against the background of intensifying globalisation driven by increasing international trade, which necessitates intercultural cooperation and negotiations, this study presents the findings of a research project that set out to explore the role of intercultural competence in international trade negotiations in the globally connected steel-related flat-rolled products industry sector. The areas of interest for the research included the identification of the features that comprise intercultural competence as well as the assessment of the role that these identified features of intercultural competence play in the international steel trade. A third research area was concerned with the assessment of the applicability of the value dimensions by Trompenaars and Hampden-Turner as the most suitable scientific model for the research setting. By employing a qualitative research approach based on six expert interviews, this study provides recommendations for Business Practice and further impulses for scientific research in the field of intercultural comepetence and cross-cultural negotiations.
Keywords: 650; intercultural competence; international trade negotiations; steelrelated flat-rolled products; value dimensions; successful business practices